Assessment of Extracellular Particles Directly in Diluted Plasma and Blood by Interferometric Light Microscopy. A Study of 613 Human and 163 Canine Samples - Korenjak, Boštjan; Tratenšek, Armando; Arko, Matevž; Romolo, Anna; Hočevar, Matej; Kisovec, Matic; Berry, Maxence; Bedina Zavec, Apolonija; Drobne, David; Vovk, Tomaž; Iglič, Aleš; Nemec Svete, Alenka; et al. (Cells (Basel, Switzerland), 2024)
Extracellular nanoparticles (EPs) are a subject of increasing interest for their biological role as mediators in cell–cell communication; however, their harvesting and assessment from bodily fluids are challenging, as processing can significantly affect samples. With the aim of minimizing processing artifacts, we assessed the number density (n) and hydrodynamic diameter (Dh) of EPs directly in diluted plasma and blood using the following recently developed technique: interferometric light microscopy (ILM). We analyzed 613 blood and plasma samples from human patients with inflammatory bowel disease (IBD), collected in trisodium citrate and ethylenediaminetetraacetic acid (EDTA) anticoagulants, and 163 blood and plasma samples from canine patients with brachycephalic obstructive airway syndrome (BOAS). We found a highly statistically significant correlation between n in the plasma and n in the blood only in the human (i.e., but not canine) blood samples, between the samples with trisodium citrate and EDTA, and between the respective Dh for both species (all p < 10−3). In the human plasma, the average was 139 ± 31 nm; in the human blood, was 158 ± 11 nm; in the canine plasma, was 155 ± 32 nm; and in the canine blood, was 171 ± 33 nm. The differences within species were statistically significant (p < 10−2), with sufficient statistical power (P > 0.8). For , we found no statistically significant differences between the human plasma and blood samples or between the samples with trisodium citrate and EDTA. Our results prove that measuring n and Dh of EPs in minimally processed fresh blood and in diluted fresh plasma by means of ILM is feasible for large populations of samples.